Enhancing Accountability through the Application of Sharia Accounting Principles: A Case Study of Baznas Makassar City - Nur Sandi Marsuni (Pustaka Digital Indonesia, 2024)
This research aims to explore Sharia Accounting Principles in Maintaining Accountability of Financial Reports in Baznas Makassar City. The research method used is qualitative with data collection through interviews and documentation. The research results show that Sharia Accounting Principles have been effectively implemented in Baznas Makassar City, starting from planning activities and budgets, collecting and receiving zakat funds to distributing and utilizing zakat funds for mustahik. From all these activities, Makassar City Baznas makes financial reports in accordance with PSAK NO. 109 as a form of accountability and updating audited financial reports to the Makassar City Baznas Official Website as a form of information transparency to interested parties. This research reveals that the management of Makassar City Baznas has carried out its duties and functions well as the Amil Zakat Agency which collects and distributes zakat, infaq and alms funds nationally in accordance with Law no. 23 of 2011. However, the Makassar City Baznas financial report does not fully refer to PSAK 109, because there is still one component of the financial report that has not been reported, namely the Changes in Asset Management report. Therefore, the research recommends that the Makassar City Baznas financial report fully refers to PSAK No. 109 in the future and carry out audit checks not only by internal auditors but also by independent auditors to increase the transparency of their financial reports.